Efektivitas Konseling Individu Dalam Meningkatkan Konsentrasi Belajar Pada Siswa Di Sanggar Kampung Pandan Malaysia - Alnamira Gunawan, Allika; Yudha Wastuti, Sri Ngayomi (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2026)
A lack of concentration among pupils leads to noise in the classroom and causes them to become easily bored whilst studying and lose focus during lessons. Through individual counselling, counsellors and teachers help pupils understand that boredom is a natural psychological response, but one that needs to be managed. They also provide guidance on active learning techniques to minimise boredom during lessons. This study aims to determine the effectiveness of individual counselling in improving students’ concentration in learning at Sanggar Kampung Pandan, Malaysia. This study employs a quantitative method with a one-group pretest-posttest design. The study was conducted in Year 1 with four students. The research method used was quantitative, involving the administration of a pretest before the service was provided and a posttest after the service was provided. The improvement in students’ learning concentration at Sanggar Kampung Pandan Melayu indicates an increase, as seen from the mean pretest score of 37.75 and the mean posttest score of 46.75. Furthermore, the t-test result showed a p-value of 0.000, thereby confirming the effectiveness of individual counselling in improving students’ learning concentration at Sanggar Kampung Pandan, Malaysia. Keywords: Individual Counselling, Concentraction, Effectiveness